Using 'draw, write and tell' to understand children's health-related experiences - Pope, Nicole; Tallon, Mary; Leslie, Gavin; Wilson, Sally (RCN Publishing Company, 2019)
BACKGROUND: In recognising the capability and rights of children to express their experiences, 'draw, write and tell' (DWT) has emerged as a participatory qualitative research method. DWT enables children to communicate their experiences by drawing, writing words and telling the story of their pictures in response to interview questions. AIM: To discuss the challenges and benefits of using DWT to explore children's experiences of pain. DISCUSSION: Aspects that affect the quality of data in DWT include the materials used and the influences of the primary caregiver. Experience suggests that if trust between the child and researcher has been established, the duration of the interview is unimportant. CONCLUSION: While many methods of analysis can be used with data gathered using DWT, it is important to ensure children's perspectives are represented accurately. Furthermore, children's capacity as active participants in research should be reflected. IMPLICATIONS FOR PRACTICE: Future studies could examine the potential of using drawings to share information in adult and paediatric clinical settings.